Limits on the Event Rates of Fast Radio Transients from the V-FASTR - Wayth, Randall; Tingay, Steven; Deller, A; Brisken, Walter; Thompson, David; Wagstaff, K; Majid, Walid (Institute of Physics Publishing Ltd., 2012)
We present the first results from the V-FASTR experiment, a commensal search for fast transient radio bursts using the Very Long Baseline Array (VLBA). V-FASTR is unique in that the widely spaced VLBA antennas provide a discriminant against non-astronomical signals and a mechanism for the localization and identification of events that is not possible with single dishes or short baseline interferometers. Thus, far V-FASTR has accumulated over 1300 hr of observation time with the VLBA, between 90 cm and 3 mm wavelength (327 MHz-86 GHz), providing the first limits on fast transient event rates at high radio frequencies (> 1.4 GHz). V-FASTR has blindly detected bright individual pulses from seven known pulsars but has not detected any single-pulse events that would indicate high-redshift impulsive bursts of radio emission. At 1.4 GHz, V-FASTR puts limits on fast transient event rates comparable with the PALFA survey at the Arecibo telescope, but generally at lower sensitivities, and comparable to the "fly's eye" survey at the Allen Telescope Array, but with less sky coverage. We also illustrate the likely performance of the Phase 1 SKA dish array for an incoherent fast transient search fashioned on V-FASTR